Recent Applications of Rare Earth Complexes in Photoredox Catalysis for Organic Synthesis - Prieto, Alexis; Jaroschik, Florian (Current Organic Chemistry, 2022)
In recent years, photoredox catalysis has appeared as a new paradigm for forging a wide range of chemical bonds under mild conditions using abundant reagents. This approach allows many organic transformations through the generation of various radical species, enabling the valorization of non-traditional partners. A continuing interest has been devoted to the discovery of novel radical-generating procedures. Over the last ten years, strategies using rare-earth complexes as either redox-active centers or as redox-neutral Lewis acids have emerged. This review provides an overview of the recent accomplishments made in this field. It especially aims to demonstrate the utility of rare-earth complexes for ensuring photocatalytic transformations and to inspire future developments.
Keywords: photocyclization